2011
DOI: 10.1002/jcc.21782
|View full text |Cite
|
Sign up to set email alerts
|

π–π interaction of quinacridone derivatives

Abstract: The π–π stacking interactions play an important role in molecular assemblies of quinacridone derivatives (QAs). In our previous work (Sun et al., J Phys Chem A 2008, 112, 11382), we have shown that quinacridone derivatives can be self-associated as dimers in solution by means of NMR study. Herein, we perform theoretical studies on the molecular interaction in the dimers of QAs to illustrate π–π interactions in terms of their strength, geometrical preference, substituent effect, and physical nature. Density fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
2
8
0
1
Order By: Relevance
“…On the contrary, the S‐series dimers nearly possess the same rotation angle ( θ = 60°), except S‐2CF3 dimer ( θ = 130°), though the vertical separation is different. As for the C‐series, it is interesting to find that the C dimer with the strongest binding interaction energy shows the optimal configuration of perfect eclipsed ( θ = 0°) molecular stacking, which generally makes the dimer less stable due to a strong electronic repulsion, especially for planar dimers . Furthermore, the optimal configuration of the C‐2CF3 dimer predicted by the calculation is in agreement with the experiment result .…”
Section: Resultssupporting
confidence: 79%
“…On the contrary, the S‐series dimers nearly possess the same rotation angle ( θ = 60°), except S‐2CF3 dimer ( θ = 130°), though the vertical separation is different. As for the C‐series, it is interesting to find that the C dimer with the strongest binding interaction energy shows the optimal configuration of perfect eclipsed ( θ = 0°) molecular stacking, which generally makes the dimer less stable due to a strong electronic repulsion, especially for planar dimers . Furthermore, the optimal configuration of the C‐2CF3 dimer predicted by the calculation is in agreement with the experiment result .…”
Section: Resultssupporting
confidence: 79%
“…Interactions that likely contribute to these favorable π–π complexes include dipole-dipole interactions [33, 34], electrostatic interactions [35, 36] and van der Waals interactions [37], as well as frontier molecular orbital interactions [38, 39]. Frontier molecular orbital theory [40] suggests that the important interactions of caffeine with the intercalating drugs will be the HOMO of caffeine and the LUMO of the antitumor agents.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, it has been recently reported that phenolic nitronylnitroxides assemble in anti-parallel arrangements in the solid state [28]. The parallel/antiparallel stacking mode has been recently analyzed computationally in quinacridone derivatives and the energetically favored antiparallel mode agrees with reported experimental NMR findings [29].…”
Section: Comparisonsmentioning
confidence: 69%